A historical perspective and opportunities for dietetics education, practice and professional organizations in the Czech Republic - Krobot, Martin; Hawk, Victoria; Spáčilová, Veronika; Kapounová, Zlata (Profese on-line, 2021)
Background: Food and nutrition play an essential role in human health. Evidence-based research supports the important role of dietitians providing medical nutrition therapy for the prevention, management and treatment of many diseases and conditions. Officially recognized in 1951, dietitians (formerly dietary nurses) have an important history in the Czech Republic. Aim: This narrative review aims to examine the history of nutrition care in the Czech Republic and identify future opportunities for the development and contributions of dietitians. We include information about education, relevant legislation, licensure, scope of practice, the current workforce, and existing professional organizations. The article provides an assessment of the opportunities for the future development and professionalization of dietitians. Methodology: We used licensed, electronic databases PUBMED, CINAHL, EBSCO, MEDVIK to search the professional literature as well as hand searching publications in both the Czech and English languages including current legislation and statistical information. Results: Formal dietetics training has progressed from the preparation of therapeutic meals to university level programs offering science-based training with supervised clinical practice to prepare bachelor’s and master’s level dietitians. As a nationally recognized profession there are three professional associations supporting more than 2,500 dietitians in the Czech Republic. Despite these developments, the advancement of the profession remains inadequate due to a limited scope of practice, wide variation in education amongst dietitians, no requirements for licensure and underutilized competencies. Conclusion: Despite the long history and development of this profession, dietitians in the Czech Republic remain an underutilized resource to provide a wide variety of nutrition services. Thus, in an effort to expand their scope of practice and improve nutrition care, further research is needed within the Czech Republic to demonstrate their essential role in the prevention, treatment and management of many diseases.
Keywords: Clinical Competence; nutriční terapeut; poskytování zdravotní péče; Delivery of Health Care; Nutrition Therapy; odborná praxe; klinické kompetence; Professional Practice; nutriční terapie; Education, Professional; vzdělávání odborné